Asst.Prof, Department of Information Technology, Vignan’s Institute of Information Technology, Duvvada, Visakhapatnam - Raju, V . Appala; Devi, G Indira; Murthy, A.Sampath Dakshina; Saikumar, K.; Jagan, B. Omkar Lakshmi (International Journal of Psychosocial Rehabilitation, 2020)
The heart is one of the major organ part that stimulatesthe blood pressure for body parts. If this heart has damaged by any diseases or infections than automatically, the body parts are inflicted. Heart diagnosis is mainly possible by MRI scan, Ultra scan and ECG machine analysis. In this research work, coronary heart diseases are identified using ultrasound imaging process. For this segmentation, feature extraction and classification has performed by advanced methodologies. This work is most useful for researchers and doctors for easy of diagnosis the heart diseases. At final calculating the performance measures i.e. Recall, F1 score, True positive rate and efficiency. Outputs are challenging the existed models and increasing the accuracy at diagnosis of the heart.